Distribution and abundance of stoneworts (Charales) in the Kashubian Lakeland (NW Poland) - data collected so far and some implications - Bociąg, Katarzyna (Biodiversity: Research and Conservation, 2006)
This work contains a list of currently known stands of 13 Charales species occurring in 63 lakes in the Kashubian Lakeland. Chara fragilis and Chara tomentosa most often grow in hard-water lakes, whereas Chara delicatula and Nitella flexilis can be found in soft-water lakes. The biggest number of stands is situated in the middle and southern parts of the Lakeland, i.e. in the area of terminal moraines and outwash plains from the latest glaciation. In the Kashubian Lakeland over half of the lakes with Charales are burdened with various effects of human pressure: 30% of the lakes are heavily exploited for recreation purposes; 20% of them undergo the process of eutrophication as a result of arable farming in their catchments; and 15% are under threat of humification. In an era of transformations caused by human intervention in ecosystems, the analysis of their flora’s condition is as important as the evaluation of physical and chemical features of water bodies.